2020
DOI: 10.1080/16583655.2020.1747767
|View full text |Cite
|
Sign up to set email alerts
|

The oil-absorbing properties of kapok fibre – a commentary

Abstract: This paper highlights the oil absorbing properties of natural and modified kapok fibres. The discussion is centred on the waxy layer and hydrophobic nature that translate the excellent oil removal performance of kapok fibre. A stirring had shown that the oil absorption by natural kapok could be greatly enhanced to over 200 g/g. For dispersed oil in wastewater, a depth filtrating system with rotatable and taper-shaped filter column with kapok fibre was reported to recover 32.3 g/g of the oils. Several modificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The unaffected hollow lumen structure of the fibers and the added surface roughness from the CaSt 2 particles provide effective space for oil sorption in the fiber assembly. The increase in surface roughness increases the surface area that anchors oil particles on the fiber surface during sorption and improves oil retention, especially during the extraction of the sorbent from the remediated media [ 25 , 46 , 47 ]. Surface area analysis using BET showed that modification increased the surface area of raw-KF (0.355 m 2 /g).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The unaffected hollow lumen structure of the fibers and the added surface roughness from the CaSt 2 particles provide effective space for oil sorption in the fiber assembly. The increase in surface roughness increases the surface area that anchors oil particles on the fiber surface during sorption and improves oil retention, especially during the extraction of the sorbent from the remediated media [ 25 , 46 , 47 ]. Surface area analysis using BET showed that modification increased the surface area of raw-KF (0.355 m 2 /g).…”
Section: Resultsmentioning
confidence: 99%
“…Although the fibers are predominantly cellulosic, their waxy surface renders them low wettability to water. Additionally, kapok fibers’ low density and excellent buoyancy make them suitable for recovering spilled oil [ 25 , 26 , 27 ]. Surface modifications are made to improve oil adhesion and retention by increasing surface roughness or coating with an oleophilic material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a significantly low value when compared to the acid/alkali-treated kapok fiber, which has a value of 23.4 mg/g. The low adsorption capacity for lead, using raw KF, can be correlated to the existence of plant wax, which makes the fiber hydrophobic [95]. The application of acid/alkali treatment In the study by Wang et al [70], the KF surface was modified by acid and alkali treatment at the conditions of pH 7.0 and 80 °C and resulted in an adsorption capacity of 23.4 mg/g for the removal of lead.…”
Section: Acid/alkaline Pretreatment Of Kapok Fibermentioning
confidence: 99%
“…This is a significantly low value when compared to the acid/alkali-treated kapok fiber, which has a value of 23.4 mg/g. The low adsorption capacity for lead, using raw KF, can be correlated to the existence of plant wax, which makes the fiber hydrophobic [ 95 ]. The application of acid/alkali treatment removes the plant wax, exposing functional groups such as hydroxyl, which has been linked to the adsorptive removal of heavy metal ions [ 70 ].…”
Section: Pre-treatments and Surface Modification Of Kapok Fibersmentioning
confidence: 99%